COSMOS: Collaborative, Seamless and Adaptive Sentinel for the Internet of Things - Nespoli, Pantaleone; Useche Pelaez, David; Díaz López, Daniel; Gómez Mármol, Felix (Suiza, 2019)
The Internet of Things (IoT) became established during the last decade as an emerging technology with considerable potentialities and applicability. Its paradigm of everything connected together penetrated the real world, with smart devices located in several daily appliances. Such intelligent objects are able to communicate autonomously through already existing network infrastructures, thus generating a more concrete integration between real world and computer-based systems. On the downside, the great benefit carried by the IoT paradigm in our life brings simultaneously severe security issues, since the information exchanged among the objects frequently remains unprotected from malicious attackers. The paper at hand proposes COSMOS (Collaborative, Seamless and Adaptive Sentinel for the Internet of Things), a novel sentinel to protect smart environments from cyber threats. Our sentinel shields the IoT devices using multiple defensive rings, resulting in a more accurate and robust protection. Additionally, we discuss the current deployment of the sentinel on a commodity device (i.e., Raspberry Pi). Exhaustive experiments are conducted on the sentinel, demonstrating that it performs meticulously even in heavily stressing conditions. Each defensive layer is tested, reaching a remarkable performance, thus proving the applicability of COSMOS in a distributed and dynamic scenario such as IoT. With the aim of easing the enjoyment of the proposed entinel, we further developed a friendly and ease-to-use COSMOS App, so that end-users can manage sentinel(s) directly using their own devices (e.g., smartphone).

El Internet de las cosas (IoT) se estableció durante la última década como una tecnología con potencialidades y aplicabilidad considerables. Su paradigma de todo lo conectado juntos penetraron en el mundo real, con dispositivos inteligentes ubicados en varios dispositivos diarios. Dichos objetos inteligentes pueden comunicarse de forma autónoma a través de una red ya existente. infraestructuras, generando así una integración más concreta entre el mundo real y el informático sistemas. En el lado negativo, el gran beneficio que trae el paradigma de IoT en nuestra vida trae simultáneamente graves problemas de seguridad, ya que la información intercambiada entre los objetos con frecuencia permanece desprotegido de atacantes malintencionados. El artículo que nos ocupa propone COSMOS (Colaborativo, Centinela adaptable y transparente para Internet de las cosas), un centinela novedoso para proteger entornos de amenazas cibernéticas. Nuestro centinela protege los dispositivos de IoT mediante múltiples anillos defensivos, resultando en una protección más precisa y robusta. Además, discutimos la implementación actual del centinela en un dispositivo básico (es decir, Raspberry Pi). Se realizan experimentos exhaustivos en el centinela, demostrando que funciona meticulosamente incluso en condiciones de mucho estrés. Cada capa defensiva es probada, alcanzando un desempeño notable, demostrando así la aplicabilidad de COSMOS en un escenario distribuido y dinámico como IoT. Con el objetivo de facilitar el disfrute del centinela propuesto, desarrollamos una aplicación COSMOS amigable y fácil de usar, para que los usuarios finales pueden administrar centinelas directamente utilizando sus propios dispositivos (por ejemplo, teléfonos inteligentes).
Keywords: Internet de las cosas; Aprendizaje automático (Inteligencia artificial); Seguridad informática; Internet of Things; Sentinel for the IoT; Intrusion detection system; Smart home; Machine learning; Malware detection; Threat intelligence